The Importance of Orthophotoplans in Cadastre Work - A. R Asatov; J. J Pirimov; K. M. Muhamadov; S. O. Bobojonov; S. F. Axtamov (International Journal on Orange Technologies, 2021)
This article is devoted to the creation of a scientific basis for the use of orthophotoplans and the use of geographic information systems (GAT) in the conduct of cadastral work.